Does Colonialism Explain Everything in North Africa? What Historians Can Bring to the Table - Isabelle Grangaud; M’hamed Oualdi (L’Année du Maghreb)
Colonialism in North Africa, because of its violence and the huge transformations it caused within its societies, shaped a historical vision of the North African past that obscured other, far more deeply rooted processes. This paper not only aims to emphasize the impact of these other, deeper historical processes, it also suggests that by taking in to account this longue durée, our analytical frameworks would be expanded and so too would our understanding of Maghreb history in general and its colonial history in particular. The first section of the paper analyzes the outlines of colonial history; it examines the limitations of the spatial framework and the timeline markers used within this field of research. The second section examines the new vistas of research opened through serious consideration of the legacy and persistent effects of early modern history in North Africa. It explores these new perspectives in terms of time and space and interpretations of North African primary sources.